El derecho de impugnación y su afectación por la imposibilidad de apelar del auto de llamamiento a juicio en el proceso penal. - Luzuriaga Ch, Verónica (2012)
The reformations carried out by the National Assembly to the Penal Adjectival Code March of 2010, 29 showing in favor of a conservative penal system, you proceeded to modify the numeral one 1 of the Art. 343, eliminating the possibility to apply the appeal resource in the call car in opinion, dictated by the Judge of Penal Guarantees in the Preparatory Audience, what is contradicted in substantial form with the established objection right in the Article 8, of the Universal Declaration of the Human rights that determines as people's essential guarantee to appeal before superior organs against acts or resolutions of public authority that affect their fundamental rights, additional to it in the Article 76, numeral 7, literal m) of the Constitution of the Republic of the Ecuador that recognizes as substantial guarantee of the due process the right of the one processed to appeal of the failure or resolution in all the procedures in that he/she decides on their rights in very clear form. Of that exposed you can deduce that one leaves in abandonment state to the actionable ones when he/she refuses the human and constitutional right of appealing from the call Car to opinion, violating this way the principle of equality of the parts, and discriminating against it with regarding the District attorney's right and of the particular accuser who in he/she practices it if they can refute decisions like it is the case of the cars of nullity, prescription of the action, stay and of inhibition by reason of incompetence that like we know they are the same judges's of penal guarantees resolutions.